2002
DOI: 10.1111/j.1348-0421.2002.tb02750.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP Regulates Cell Death of Lymphocytes and Monocytes Induced by Membrane‐Bound Lipoproteins of Mycoplasma fermentans and Mycoplasma salivarium

Abstract: The cytotoxicities of lipoproteins of Mycoplasma fermentans and Mycoplasma salivarium to a lymphocytic cell line, MOLT‐4, and a monocytic cell line, HL‐60, was upregulated by ATP added extracellularly in a dose‐dependent manner. These lipoproteins induced ATP release and plasma membrane permeability increase in these cell lines. In addition, periodate‐oxidized ATP, an antagonist for P2X purinergic receptors, suppressed the cytotoxicity of the lipoproteins, suggesting the possibility that P2X receptors for ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…A number of studies have shown that T cells can release ATP in response to various extracellular stimuli, suggesting that purinergic signalling may indeed play an active role in T cell activation 8, 80, 81 . T cells express many members of the P2X, P2Y, and P1 receptor families as well as ENTPD1 82-84 .…”
Section: Purinergic Activation Of Immune Cell Responsesmentioning
confidence: 99%
“…A number of studies have shown that T cells can release ATP in response to various extracellular stimuli, suggesting that purinergic signalling may indeed play an active role in T cell activation 8, 80, 81 . T cells express many members of the P2X, P2Y, and P1 receptor families as well as ENTPD1 82-84 .…”
Section: Purinergic Activation Of Immune Cell Responsesmentioning
confidence: 99%
“…Into and coworkers found that lipoproteins of Mycoplasma fermentans and Mycoplasma salivarius induced an increase in plasma membrane permeability by which ATP is released. This extracellular ATP regulates the cytotoxicity of the lipoproteins, probably by interaction with ATP receptors such as P2X purinergic receptors (15). It has been demonstrated that extracellular ATP has profound effects on cellular functions, causing plasma membrane depolarization, Ca 2ϩ influx, and cell death (6,41).…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact molecular pathogenesis of M. genitalium is vague [7]. It has been suggested that during mycoplasmal infection, the damage to host cells is not caused by direct lesion but by immunopathogenesis [810]. Lipoproteins (LPs) are important proteins exposed on the surface of M. genitalium .…”
Section: Introductionmentioning
confidence: 99%